Seismic fragility curves of steel structure industrial building using IDA method. Issue 1 (June 2020) - Arjuna, Norazah; Adnan, Azlan; Ramli, Mohd Zamri; Aizon, Nabila Huda; Alel, Nurasmawisham; Muhammad Yuzir, Muhamad Ali; Bakar, Nabilah Abu
Abstract: Recent natural disaster events have caused damage to structures and led to loss of lives. Steel structure industrial building is one of the important structures that needs to be examined as these structures can have huge impact on the surrounding areas. Therefore, this study presents the fragility curves and performance curves of steel structure industrial building under earthquake loading. The structure consisted of beam, column, and bracing were modelled using three dimensional finite element modelling. The fragility curves were obtained for the structure, and the performance curves were developed based on lateral load, which was affected by the geometry of the building. Three records of far-field ground motion and three records of local ground motion were used for incremental dynamic analysis (IDA). The five levels of performance stated by FEMA-273, namely, operational phase (OP), immediate occupancy (IO), damage control (DC), life safety (LS), and collapse prevention (CP) were used as main guidelines to evaluate the structural performance. Results showed that, probability damage for operational phase, OP started at 0.19g and 5% of the structure analysed are expected to have immediate occupancy IO, indicating minor cracks to the structure at 0.4g PGA. Moreover, the performance response of the structure to the earthquake was obtained from the study.